Rights of children and young people - Healey, Justin (Thirroul, NSW : The Spinney Press, 2021)
Children & young people have a fundamental right to be heard and taken seriously about matters affecting them. They have the same general human rights as adults, but also possess specific rights that recognise their special needs and potential. This book explains how these rights are set out in the United Nations Convention on the Rights of the Child. It also examines the state of children's rights in Australia, where there have been some positive developments, but also a number of critical issues and mixed results.
Children's rights explained -- Children's rights in Australia.
Includes bibliographical references and index.
Keywords: Convention on the Rights of the Child -- (1989 November 20) -- Juvenile literature; Convention on the Rights of the Child; Convention on the Rights of the Child -- (1989 November 20); Children's rights; Human rights; Youth -- Civil rights; Youth -- Civil rights -- Australia; Human rights -- Australia; Children's rights -- Australia; Children -- Legal status, laws, etc; Children's rights -- Juvenile literature; Australia; Australian